A Randomized, Comparative Study to Evaluate Efficacy and Safety of Two Injection Volumes of AbobotulinumtoxinA in Treatment of Glabellar Lines. Issue 8 (August 2016) - Punga, Anna Rostedt; Alimohammadi, Mohammad; Fagrell, Dan; Nyberg, Frida; Rees, Diane; Wong, Cindy
Abstract : BACKGROUND: Different volumes of 0.9% NaCl may be used to reconstitute abobotulinumtoxinA yielding an injection volume that ranges from 0.05 to 0.1 mL per injection point for treatment of glabellar lines. OBJECTIVE: To evaluate the efficacy, safety, and subject satisfaction of 2 different injection volumes to deliver the same unit dose of abobotulinumtoxinA for treatment of glabellar lines. MATERIALS AND METHODS: This randomized comparative study was conducted using 2 different reconstitution volumes to deliver a fixed unit dose of 10 Speywood units (sU) of abobotulinumtoxinA in either 0.05 mL (labeled volume) or 0.1 mL (twofold volume) per injection point. Evaluations included wrinkle severity, neurophysiological assessment by compound muscle action potential (CMAP), and subject satisfaction. RESULTS: Use of either injection volume of abobotulinumtoxinA resulted in the early onset of effect, high effectiveness, and long duration of effect. The safety profile and injection pain levels were similar in both groups. The twofold injection volume was shown to be noninferior to the labeled injection volume based on CMAP results. CONCLUSION: A twofold increase in injection volume to 0.1 mL per injection point to deliver 10 sU of abobotulinumtoxinA is effective and safe.